Functional Conservation of P48/45 Proteins in the Transmission Stages of Plasmodium vivax (Human Malaria Parasite) and P. berghei (Murine Malaria Parasite) - Yi Cao (American Society for Microbiology, 2018)
ABSTRACT Sexual-stage proteins have a distinct function in the mosquito vector during transmission and also represent targets for the development of malaria transmission-blocking vaccine. P48/45, a leading vaccine candidate, is critical for male gamete fertility and shows >50% similarity across various species of Plasmodium. We evaluated functional conservation of P48/45 in Plasmodium vivax and P. berghei with the motivation to establish transgenic P. berghei strains expressing P. vivax P48/45 (Pvs48/45) in an in vivo assay to evaluate the transmission-blocking activity of antibodies elicited by Pvs48/45. Homologous recombination was employed to target P. berghei s48/45 (pbs48/45) for knockout (KO) or for its replacement by two different forms of P. vivax s48/45 (pvs48/45) (the full-length gene and a chimeric gene consisting of pbs48/45 5′ signal and 3′ anchor sequences flanking pvs48/45). Expression of Pvs48/45 in transgenic parasites and lack of expression of any P48/45 in KO parasites were confirmed by reverse transcription-PCR (RT-PCR) and Western blotting. Both transgenic and knockout parasites revealed asexual growth kinetics in mice comparable to that seen with wild-type parasites. When employed in mosquito infection experiments, both transgenic parasite strains remained transmission competent and developed into infectious sporozoites, whereas the knockout parasites were incapable of establishing mosquito-stage infection. These results indicate the functional conservation of P48/45 protein during transmission, and the transgenic parasites generated in this study represent a valuable tool to evaluate the protective efficacy of transmission-blocking antibodies elicited by Pvs48/45-based vaccines using an in vivo mouse animal assay instead of ex vivo membrane feeding assays (MFA) relying on access to P. vivax gametocytes from infected patients. IMPORTANCE Malaria transmission depends upon successful sexual differentiation and maturation of parasites in the vertebrate host and further development in the mosquito midgut. Stage-specific proteins in the sexual stages have been shown to play a critical role in development and successful transmission through the anopheline mosquito vector. Studies presented in the current manuscript evaluated functional conservation of one such protein, P48/45, in two diverse species (P. berghei and P. vivax). Replacement of endogenous pbs48/45 in P. berghei with pvs48/45 (P. vivax homologue) did not affect the viability of the parasites, and the transgenic parasites expressing Pvs48/45 remained transmission competent. These studies establish not only the functional conservation of P48/45 in P. berghei and P. vivax but also offer an opportunity to develop an in vivo test model for Pvs48/45-based P. vivax transmission-blocking vaccines, currently under development.